Conditions for higher methanol selectivity for partial CH4 oxidation over Fe-MOR using N2O as the oxidant and comparison to Fe-SSZ-13, Fe-SSZ-39, Fe-FER, and Fe-ZSM-5 - Gokce, Iklim; Ozbek, M. Olus; Ipek, Bahar (Academic Press Inc Elsevier Science, 2023)
Continuous catalytic conversion of methane to methanol was investigated on Fe-MOR at atmospheric pressure and moderate temperatures (270-300 degree celsius) with an emphasis on improving the methanol selectivity. Results showed a relation between the methanol selectivity, iron content and mesopore addition on Fe-MOR as well as H2O concentration in the feed. Decreasing the iron content of Fe-MOR, adding mesopores to MOR or increasing water vapor pressure from 3 to 21 kPa gave higher methanol selectivity. Addition of mesopores suppressed the over-oxidation products (CO and CO2) and coke formation significantly, resulting in an increased catalyst lifetime as well as higher methanol turnover frequency (2.0 vs. 3.9 h-1 at 320 degree celsius). Using DFT methods several active site candidates were analyzed regarding their formation energies, UV-Vis spectra and methanol formation pathways. DFT studies suggest that [Fe2O2](2+ )or [HOFe(mu-O)FeOH](2+) sites on the 8 member rings are active for direct methane to methanol conversion.
Keywords: Direct methane to methanol; N2O; Mesoporous zeolites; Fe-MOR; DFT; [HOFe(mu-O)FeOH](2+)